Efektivitas Teknologi Pembelajaran Dalam Menumbuhkan Minat Siswa Belajar Pendidikan Agama Islam (PAI) - Kumala Sari, Eva Dwi (Almarhalah | Jurnal Pendidikan Islam, 2017)
Learning technology is one of the important components in supporting the learning process. So that the learning process becomes more conducive. Likewise, the teaching and learning process in the field of Islamic Religious Education studies, learning activities in that field can be applied with learning technology in order to foster student interest in learning the field of Islamic Religious Education studies. This study aims to obtain empirical data on the Effectiveness of Learning Technology in Growing Student Interest in Learning Islamic Religious Education. So that it can obtain the effectiveness caused in the process of teaching and learning students who use technology and who do not use learning technology. This research was conducted on students of class VIII at SDI Tahta Syajar Bekasi. Writing this article uses several data collection techniques including observation, interviews, literature studies, and questionnaires. While the method used is descriptive quantitative method, with sampling using random sampling, about 20% consisting of 86 students from the existing population. Then start by testing different respondent instruments. After that spread the test that has been tested, the variables examined are the Effectiveness of Learning Technology as the independent variable, and the interest of students learning PAI as the dependent variable. Data analysis using Product Moment correlation. The results of the calculation of the Effectiveness of Learning Technology in the mean empirical score of 105.69 mean theoretical score of 72.50 thus the reality of the results of the Learning Technology Effectiveness score is categorized high. and the mean empirical score on PAI learning interest in can be 129.90 80 from the mean theoretical score so the reality score of Islamic Education Learning Interest Interest is categorized high. Whereas, for the normality test of Learning Technology Effectiveness obtained, Lhitung = 0.072 0.096 = Ltabelmaka, the null hypothesis is accepted, for the interest in learning PAI, it is obtained Lhitung = 0.048 0.096 = Ltabelmaka, the null hypothesis is accepted, meaning that both variables are normally distributed. To calculate the product moment correlation coefficient can be calculated r by 0.619 which there is a positive correlation between variable X and Y. Continue the t-student test because tcount = 7.22 2.00 = t (0.975) (86), then the hypothesis zero rejected. This means that there is a significant relationship between variable X with variable Y. And the results of the calculation of the coefficient of determination of 0.3831 this means that learning technology contributes 38.31% to the interest in learning PAI, while 61.69% of other factors.